2007
DOI: 10.1111/j.1872-034x.2007.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of portal vein tolerance

Abstract: The liver has been considered as a tolerogenic organ in the sense that favors the induction of peripheral tolerance. The administration of antigens (Ags) via the portal vein causes tolerance, which is termed portal vein tolerance and can explain the occurrence of tolerogenic responses in the liver. Here we discuss the fundamental mechanisms accounting for portal vein tolerance. Antigen-presenting cells (APCs) in the liver, especially dendritic cells and sinusoidal endothelial cells, have limited the ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
0
8
0
1
Order By: Relevance
“…This in return could result in tissue damage in various organs leading to early death. In contrast to the spleen, antigen presentation in the liver induces tolerance, known as portal vein tolerance [41]. Indeed, we observed that resistant mice had significantly higher luciferase expression in the liver than susceptible mice.…”
Section: Discussionmentioning
confidence: 75%
“…This in return could result in tissue damage in various organs leading to early death. In contrast to the spleen, antigen presentation in the liver induces tolerance, known as portal vein tolerance [41]. Indeed, we observed that resistant mice had significantly higher luciferase expression in the liver than susceptible mice.…”
Section: Discussionmentioning
confidence: 75%
“…Our study reveals a hierarchy of factors dictating the fate of CD8 T cells during hepatic immune responses, and provides an explanation for the different immune outcomes observed in a variety of immune-mediated liver pathologic conditions. rAAV | CTL | TCR | cytotoxicity T he liver is acknowledged to possess unique tolerogenic properties, which have likely evolved to maintain immunological unresponsiveness toward food-derived and microbial antigens that enter the circulation via the gut (1,2). This tolerogenic capability of the liver is demonstrated in animal models of liver transplantation, in which liver allografts are accepted across complete MHC mismatch barriers and are able to protect other donor tissues from rejection (reviewed in ref.…”
mentioning
confidence: 99%
“…The procedures are in accordance with the Helsinki Declaration of 1975. CD14 + monocytes (1 × 10 6 /mL) were isolated from PBMCs using CD14 microbeads (Miltenyi Biotec, Gladbach, Germany) and were cultured for 16 h in complete RPMI medium in the presence of peptidoglycan (PGN, 10 μg/mL, InvivoGen, San Diego, CA, USA) or lipopolysaccharide (LPS, 1 μg/mL, Sigma‐Aldrich, St. Louis, MO, USA) as previously described . Cells were stained with phycoerythrin (PE)‐conjugated CD14 antibody (eBioscience, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Monocytes (1 × 10 6 /mL) were cultured for 16 h in complete RPMI medium in the presence of PGN (10 μg/mL) or LPS (1 μg/mL). Culture supernatants were subjected to enzyme‐linked immunosorbent assay (ELISA) for the measurement of tumor necrosis factor‐α (TNF‐α) and interleukin‐10 (IL‐10) (BD Bioscience) as described previously .…”
Section: Methodsmentioning
confidence: 99%